An ultra-thin, un-doped NiO hole transporting layer of highly efficient (16.4%) organic–inorganic hybrid perovskite solar cells. Issue 22 (24th May 2016) - Seo, Seongrok; Park, Ik Jae; Kim, Myungjun; Lee, Seonhee; Bae, Changdeuck; Jung, Hyun Suk; Park, Nam-Gyu; Kim, Jin Young; Shin, Hyunjung
Abstract : ALD-grown ultra-thin NiO HTLs were optimized by Debye length ( L D ) overlapping and demonstrated to be efficient HTLs for perovskite solar cells. Abstract : NiO is a wide band gap p-type oxide semiconductor and has potential for applications in solar energy conversion as a hole-transporting layer (HTL). It also has good optical transparency and high chemical stability, and the capability of aligning the band edges to the perovskite (CH3 NH3 PbI3 ) layers. Ultra-thin and un-doped NiO films with much less absorption loss were prepared by atomic layer deposition (ALD) with highly precise control over thickness without any pinholes. Thin enough (5–7.5 nm in thickness) NiO films with the thickness of few time the Debye length ( L D = 1–2 nm for NiO) show enough conductivities achieved by overlapping space charge regions. The inverted planar perovskite solar cells with NiO films as HTLs exhibited the highest energy conversion efficiency of 16.40% with high open circuit voltage (1.04 V) and fill factor (0.72) with negligible current–voltage hysteresis.